Drought Has a Greater Negative Effect on the Growth of the C3 Chenopodium quinoa Crop Halophyte than Elevated CO2 and/or High Temperature - Rakhmankulova, Zulfira; Shuyskaya, Elena; Prokofieva, Maria; Toderich, Kristina; Saidova, Luizat; Lunkova, Nina; Voronin, Pavel (Plants, 2024)
Plant growth and productivity are predicted to be affected by rising CO2 concentrations, drought and temperature stress. The C3 crop model in a changing climate is Chenopodium quinoa Willd—a protein-rich pseudohalphyte (Amaranthaceae). Morphophysiological, biochemical and molecular genetic studies were performed on quinoa grown at ambient (400 ppm, aCO2) and elevated (800 ppm, eCO2) CO2 concentrations, drought (D) and/or high temperature (eT) treatments. Among the single factors, drought caused the greatest stress response, inducing disturbances in the light and dark photosynthesis reactions (PSII, apparent photosynthesis) and increasing oxidative stress (MDA). Futhermore, compensation mechanisms played an important protective role against eT or eCO2. The disruption of the PSII function was accompanied by the activation of the expression of PGR5, a gene of PSI cyclic electron transport (CET). Wherein under these conditions, the constant Rubisco content was maintained due to an increase in its biosynthesis, which was confirmed by the activation of rbcL gene expression. In addition, the combined stress treatments D+eT and eCO2+D+eT caused the greatest negative effect, as measured by increased oxidative stress, decreased water use efficiency, and the functioning of protective mechanisms, such as photorespiration and the activity of antioxidant enzymes. Furthermore, decreased PSII efficiency and increased non-photochemical quenching (NPQ) were not accompanied by the activation of protective mechanisms involving PSI CET. In summary, results show that the greatest stress experienced by C. quinoa plants was caused by drought and the combined stresses D+eT and eCO2+D+eT. Thus, drought consistently played a decisive role, leading to increased oxidative stress and a decrease in defense mechanism effectiveness.